The Oxford Map Companion : One Hundred Sources in World History - Seed, Patricia (New York Oxford University Press, 2014)
Bringing together a rich and diverse collection of 100 historical maps from the Palaeolithic to the present, The Oxford Map Companion: One Hundred Sources in World History illustrates how peoples and cultures throughout the human past have imagined their worlds. The collection - which includes many never-before published maps - spans a broad spectrum of human time and cultural diversity
Include Color Illustration, Map and Index
Keywords: World history -- World maps -- Atlases